Strengthening the Capacity of Village Government Officials in Negeri Suli, Salahutu District, Central Maluku Regency - Rahanra, Ivonny Yeany; Soselisa, Pieter Sammy; Ponto, Iriane Sosiawaty; Sakir, Ahmad Rosandi (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This community service activity aimed to strengthen the capacity of village government officials in Negeri Suli, Salahutu District, Central Maluku Regency. The main issue addressed was the limited skills and knowledge of officials in governance, administration, financial management, public service, and technology utilization, which affect the efficiency and accountability of village administration. Method: The program was conducted through a combination of training, workshops, technical guidance, simulations, and hands-on exercises. Participants engaged in practical exercises for document management, budgeting, public service delivery, and the use of digital tools. Feedback and evaluations were incorporated to monitor progress and improve learning outcomes. Practical Applications: The results enhanced officials’ ability to plan, implement, and monitor village programs effectively. Improved administrative skills, financial transparency, and digital literacy allow for more efficient service delivery, better community engagement, and accountable governance. Conclusion: The program successfully strengthened the competence of village officials, promoting efficient, transparent, and citizen-oriented administration, providing a sustainable foundation for future village development initiatives.